Violence Victimization and Alcohol Use Among Venue-Based Female Sex Workers in Pattaya, Thailand: Unpacking the Temporal Relationship - Sherwood J. (2023)
Female sex workers (FSWs) face prevalent violence victimization and alcohol consumption at work, yet the bidirectional pathways between these factors are not well defined. Using cohort data from 232 venue-based FSWs in Pattaya, associations of violence and alcohol use were examined within a time period and prospectively via structural equation models. Within the time period, violence victimization and alcohol use were consistently associated; by contrast, violence was not prospectively associated with FSW alcohol use. Findings define alcohol as an important risk factor for violence in sex work environments. Alcohol safety interventions should be explored as a vital component of FSW violence prevention.